Presenting, (re)constructing and arranging medieval artefacts from non-religious and religious contexts - Roggenkamp, Antje (Poligrafi, 2024)
The influence of digitalised images on individual and societal life has become considerable. The digital media revolution exercises a particular impact on the way we engage with works of art. In contrast to other educational institutions, museums structure the relationship to the past primarily through the arrangement of objects and artefacts, and they ensure that religious and non-religious cultural heritage is preserved. However, the emergence of digital technologies is changing the self-image of museums. Even though digital copies are playing an important role for presenting medieval artefacts, there are still hardly any criteria to determine their use in muse-ums. In this regard, the present study begins with a practice-orientated re-reading of Walter Benjamin’s classic essay “The Work of art in the age of its Technological Reproducibility”. Benjamin’s essay focuses on the aura of an original work of art, which changes when it is technologically reproduced. In a practice-orientated re--reading, Benjamin’s aura can be considered from different aspects: as practices of describing, seeing and comparing. From this perspective, a deeper re-reading takes these practices as a starting point for developing further criteria: modes of presen-ting, (re)constructing and arranging. as a result, the application of these practices and criteria opens up new perspectives not only for engaging with works of art and their technologically reproduced copies, but also for digital copies. Two case studies will be used to examine whether and to what extent the crite-ria gained by re-reading Benjamin’s essay are suitable for facilitating the accessibi-lity of artefacts through digital copies. The chosen artefacts date from the period to which Benjamin ascribes the largest dense aura – the Middle ages: the Bayeux Tapestry and the Halderner altar.
Keywords: (religious) materiality; (religious) work of art; (religiozna materialnost); (religiozna) umetniška dela; Bayeux tapestry; digital copy; digitalna kopija; Halderner altar; izvirni artefakti; mechanical produced copy; mehanska kopija; oltar iz Halderna; original artefacts; practice-theoretical approach; praktično-teoretični pristop; tapiserija iz Bayeuxa